A global investigation into the back pain attitudes and beliefs of human factors and ergonomics specialists - Du Plessis, Abigail Gillian (https://orcid.org/0009-0001-0813-4439) (Rhodes University, 2026)
Background: Lower back pain (LBP) is highly prevalent within working contexts globally and evidently has a negative impact on the well-being and performance of workers. Unhelpful attitudes and beliefs about back pain, through complex interactions, contribute to the persistence of LBP and related disability. Professionals have the potential to transmit their own views to others through belief-driven advice and recommendations. The attitudes and beliefs of human factors and ergonomics (HFE) specialists are currently unknown but have the potential to influence the attitudes, beliefs, and behaviours of workers and other company stakeholders. This study aimed to address this gap through an investigation into the back pain related attitudes and beliefs of global HFE specialists, including the International Ergonomics Association’s (IEA) Council. Method: The validated Back Pain Attitudes Questionnaire (Back-PAQ) was used to assess attitudes and beliefs about back pain. Data were collected at the International Ergonomics Association’s 22nd Triennial Congress held in Jeju, South Korea, and via email through IEA federated and affiliated societies. Descriptive statistics and frequency results were used to explore the attitudes and beliefs of global HFE specialists, and inferential statistics were used to determine any differences related to role and in terms of years of experience. The attitudes and beliefs of the IEA Council were subsequently compared to the rest of the sample. Results: 158 questionnaires were returned, 38 of which were from the IEA Council, providing data from HFE specialists across 27 countries. Unhelpful beliefs relating to the need for protective mechanisms and the special nature and impact of back pain were frequently identified. Conversely, the sample held positive beliefs around the relationship between pain and injury, back pain prognosis, and the need to remain active during pain episodes. The attitudes and beliefs of HFE specialists in this study were, however, highly variable with several contradictions identified. Conclusions: While some positive beliefs were identified, the negative and contradictory beliefs held may undermine advancements in HFE research, education, and practice and have the potential to perpetuate similar attitudes and beliefs in others. Further research is necessary to develop tailored interventions that address these unhelpful beliefs in specific contexts. Such efforts may improve the implementation of evidence-based prevention efforts in the workplace.
Keywords: Human engineering (http://id.loc.gov/authorities/subjects/sh85062867); Health attitudes (http://id.loc.gov/authorities/subjects/sh85059529); Human Kinetics and Ergonomics; Human factors (https://www.wikidata.org/wiki/Q121029188); Lower back pain (https://www.wikidata.org/wiki/Q852163)